KENAKALAN REMAJA DI KECAMATAN KAMPAR TIMUR (Studi Kasus SMAN 1 Kampar Timur Kecamatan Kampar Timur Kabupaten Kampar) - Harli Madi Saputra; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Senior High School 1 East Kampar, East Kampar District,Kampar Regency. With the formulation of the problems that are (1) Whatever formsmisbehavior teenagers students in Senior High School 1 East Kampar ? What factors thatcause the behavioral issues students in east Senior High School 1 East Kampar ? .The purposeof this evaluation to understand penetian forms juvenile delinquency and the factors thatcause the behavioral issues in Senior High School 1 East Kampar .Was used in the study aqualitative approach through a method of descriptive. In this research the use writers thesubject by means of purposive sample . With the source is grade 2of Senior High School 1East Kampar. The result can be seen shapes misbehavior teenager Senior High School 1 EastKampar is (a) a fight , ( b ) smoking , ( c ) home late one night , ( d ) speedway, ( e ) did notfollow school rules , ( f ) ditching from school . Factors that cause the teen studentsmisbehavior this is: external factors , first is the family and the second is secondaryenvironmental factors such as their peers and people about .The internal factor coveringsearch identity and control teens .Keywords: the teenager, deviations, delinquency, East Kampar